THE INFLUENCE OF PROFITABILITY, LIQUIDITY, NET CASH FLOWS, DIVIDEND POLICY, FIRM SIZE TO STOCK PRICE: EMPIRICAL STUDY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2015-2018 - Irawan, Tengkoe; Suryati, Evi (International Journal of Business and Information Technology, 2021)
This study was conducted to determine the effect of profitability, liquidity, net cash flow, dividend policy and firm size to stock prices at manufacturing companies listed on the Indonesia Stock Exchange. Data analysis based on normality test, Heteroskedasticity test, multicollinearity test and autocorrelation test are met, multiple linear regression analysis where profitability, liquidity, net cash flows and firm size have positive effect while dividend policy has negative effect on stock price, Partial Test (t test) where the variable profitability and firm size affect the stock price while the liquidity variable, net cash flow and dividend policy does not affect the stock price. In the F test (Simultaneous Test) the independent variables (profitability, liquidity, net cash flow, dividend policy and firm size) together have a significant effect on the dependent variable (stock price). In the coefficient of determination test (adj R2) that the dependent variable can be explained by the independent variable with the value of adj R2 of 54.5% while the remaining 45.5% influenced other variables not examined in this study